2019
DOI: 10.1063/1.5111129
|View full text |Cite
|
Sign up to set email alerts
|

A tensorial shear stress sensor based on light-emitting GaN nanopillars

Abstract: A force sensor capable of detecting both the magnitude and direction of the shear stress is proposed and demonstrated. The structure is based on an array of gallium nitride (GaN) light-emitting nanostructures and an off-the-shelf imager. The directional sensitivity originates from symmetry breaking of the nanostructures. Only a common bias is required for all GaN elements, making two-dimensional mapping of the stress relatively simple. As the stress sensing relies only on differential measurements, no stringen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Recently, a method of measuring the shear force based on gallium nitride (GaN) nanostructures was reported . Instead of inducing a change of resistance or capacitance, the device used optically active piezoelectric nanostructures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, a method of measuring the shear force based on gallium nitride (GaN) nanostructures was reported . Instead of inducing a change of resistance or capacitance, the device used optically active piezoelectric nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…To apply the shear force, a stress applicator was fabricated by patterning a square of photoresist (SPR220; 2.2 μm) on a sapphire wafer using optical lithography. The photoresist was then exposed again to ultraviolet light to render it transparent to visible wavelengths …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[244,245] For mechanical sensing in extreme conditions, WBG semiconductor nanowires of SiC, group III-nitrides, and diamond are the material of choice due to their outstanding electrical properties, chemical inertness, mechanical durability and especially, a tunable giant piezoresistive effect. [246][247][248][249][250] For instance, Gao et al reported the piezoresistance behaviors of single p-type 6H-SiC nanowires under different compressive stresses using a conductive AFM as the test bed. [246] The authors observed the decrease of the nanowire resistance with increasing compressive strain.…”
Section: Strain Sensorsmentioning
confidence: 99%